Pembaruan Hukum Islam Melalui Metode Penetapan Fatwa Majelis Tarjih Muhammadiyah - Ending Solehudin (STAI Siliwangi Bandung, 2015)
Muhammadiyah is one of the largest Islamic organizations in Indonesia.The contribution of Muhammadiyah to the development of the Indonesian nation in various community development is unquestionable, both in the period before independence, after independence, and in the present. One of them is the contribution in community development through the renewal of Islamic law. This can be seen in the legal fatwas issued by the Tarjih Muhammadiyah Council. These fatwas are answers and solutions to overcome problems faced by society that arise as a result of modern social, cultural, thought, scientific and technological developments. In the ijtihad process to establish legal fatwas, the Tarjih Muhammadiyah Council has its own methodology, which allows to be able to establish laws by adhering to the Qur'an and al-Sunnah on the one hand, and on the other hand being able to adjust the essence of the content of these legal sources to the development of modern thought, social, cultural, scientific and technological.